(untitled) (Indian Journal of Public Health Research & Development, 2020)
The present study was conducted to investigate the ability of bacteria to reduce Graphene Oxide (GO) sheets. Out of 82 bacterial isolates screened, one isolate was selected as a biological model for biosynthesis of reduced graphene oxide (RGO) nanosheets. This isolate was identified by morphological, biochemical tests, VITEK2 System, and 16S rRNA gene sequencing, aligned and submitted to the NCBI, and confirmed as Escherichia coli strain E-NO.7 (accession no. MK685205). The UV-vis. absorption peak was around 284 nm. The SEM images revealed thin, wrinkled, closely associated nanosheets. The weight percentage of carbon was 82.00% and oxygen was 18.00%. XRD analysis exhibited a broad diffraction peak at 2?= 26.5° corresponding to the interlayer spacing of 0.34 nm. The FTIR spectrum showed decrease in peaks associated to oxygen functional groups, while other peaks vanished completely.